Cut-and-Paste Transposons in Fungi with Diverse Lifestyles. (8th December 2017) - Muszewska, Anna; Steczkiewicz, Kamil; Stepniewska-Dziubinska, Marta; Ginalski, Krzysztof
Abstract: Transposable elements (TEs) shape genomes via recombination and transposition, lead to chromosomal rearrangements, create new gene neighborhoods, and alter gene expression. They play key roles in adaptation either to symbiosis in Amanita genus or to pathogenicity in Pyrenophora tritici-repentis . Despite growing evidence of their importance, the abundance and distribution of mobile elements replicating in a "cut-and-paste" fashion is barely described so far. In order to improve our knowledge on this old and ubiquitous class of transposable elements, 1, 730 fungal genomes were scanned using both de novo and homology-based approaches. DNA TEs have been identified across the whole data set and display uneven distribution from both DNA TE classification and fungal taxonomy perspectives. DNA TE content correlates with genome size, which confirms that many transposon families proliferate simultaneously. In contrast, it is independent from intron density, average gene distance and GC content. TE count is associated with species' lifestyle and tends to be elevated in plant symbionts and decreased in animal parasites. Lastly, we found that fungi with both RIP and RNAi systems have more total DNA TE sequences but less elements retaining a functional transposase, what reflects stringent control over transposition.